Hope in children with cancer: A narrative review and a concept synthesis - Kodchakon Piasai; Sasitorn Phumdoung; Songsuda Muenthaisong; Natchira Winitchai; Windy Rakhmawati (Jurnal Keperawatan Padjadjaran, 2024)
Background: Hospitalized children with cancer encounter pain, suffering, fear, and life-threatening situations which can cause them to feel hopeless. Purpose: The aims of this study are to acquire new insights about the concept of hope in children with cancer and to identify the attributes, antecedents, and consequences of hope in children with cancer. Methods: Nine English and Thai-language studies that discussed the hope in children or adolescents with cancer were located using the online database in nursing (1990–2023). Qualitative analysis and synthesis of these studies were completed using an adaptation of Walker and Avant’s concept synthesis method. Results: The antecedents of hope of children with cancer were hope of other persons surrounding them and the relationship between these children and others. The attributes of hope in children with cancer were hope for cure, intentional hope and inner strength. Also, the consequences of hope in children with cancer were well-being, quality of life, coping behavior, expressing new feelings of safety or comfort, and conveying trust to others. Conclusions: This study found that hope is important and has a positive effect on body-mind and the emotions of children with cancer. Thus, healthcare providers such as nurses should enhance hope in children with cancer by promoting their inner resources, positive experiences, and emotional support, while decreasing negative emotional factors. Therefore, children with cancer have hope in their treatment outcomes and inner strength, leading to their expressing new feelings of safety and a good quality of life.